Aerobic Physical Exercise Improves Exercise Tolerance and Fasting Glycemia Independent of Body Weight Change in Obese Females - Boschetti, Daniela; Muller, Cynthia R.; Américo, Anna Laura V.; Vecchiatto, Bruno; Martucci, Luiz Felipe; Pereira, Renata O.; Oliveira, Cláudia P.; Fiorino, Patricia; Evangelista, Fabiana S.; Azevedo-Martins, Anna Karenina (Frontiers in Endocrinology, 2021)
Obesity is associated with increased risk of several chronic diseases and the loss of disease-free years, what has increased the focus of much research for the discovery of therapy to combat it. Under healthy conditions, women are more likely to accumulate fat in subcutaneous deposits. However, this sexual dimorphism tends to be lost in the presence of comorbidities, such as type 2 diabetes mellitus (T2DM). Aerobic physical exercise (APE) has been applied in the management of obesity, however, is still necessary to better understand the effects of APE in obese female. Thus, we investigated the effect of APE on body weight, adiposity, exercise tolerance and glucose metabolism in female ob/ob mice. Eight-week-old female wild-type C57Bl/J6 and leptin-deficient ob/ob mice (Lepob) were distributed into three groups: wild-type sedentary group (Wt; n = 6), leptin-deficient sedentary group (LepobS; n = 5) and leptin-deficient trained group (LepobT; n = 8). The LepobT mice were submitted to 8-week of aerobic physical exercise (APE) at 60% of the maximum velocity achieved in the running capacity test. The APE had no effect in attenuating body weight gain, in reducing subcutaneous and retroperitoneal white adipose tissue (SC-WAT and RP-WAT, respectively) and interscapular brown adipose tissue (iBAT) weights, neither improved glucose intolerance nor insulin resistance in the LepobT group. Also, the APE did not reduce the diameter and the area of RP-WAT adipocytes, but the APE reduced the diameter and the area of SC-WAT adipocytes, which was associated with lower fasting glycemia and islet/pancreas area ratio in the LepobT group. In addition, the APE increased exercise tolerance and this response was also associated with lower fasting glycemia in the LepobT group. In conclusion, the later beginning of APE with a more severe degree of obesity did not attenuate the excessive body weight gain, however the APE promoted benefits that can improve the female health, and for this reason it should be recommended as a non-pharmacological therapy for obesity.